1993
DOI: 10.1093/carcin/14.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of oncoproteins in non-small cell lung carcinomas of smokers

Abstract: Non-small cell lung carcinoma specimens of 173 previously untreated patients were analyzed for the expression of proteins encoded by the oncogenes c-myc, c-fos, c-jun, c-erbB-1, c-erbB-2, c-H-ras, c-K-ras and c-N-ras. Forty-six per cent of the tumors were positive for the c-MYC protein, 60% for c-FOS, 50% for c-JUN, 80% for c-ERBB-1, 55% for c-ERBB-2, 12% for c-H-RAS, 5% for c-K-RAS and 71% for c-N-RAS. Proteins encoded by c-fos and c-jun are overexpressed more frequently in carcinomas of smokers (c-fos: P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…It is well known that oncogenes such as K-ras, c-myc and c-jun are often activated or overexpressed in human lung cancers (Wodrich and Volm, 1993;Szabo et al, 1996;Osada and Takahashi, 2002). However, the functional consequences of such oncogene activation in the development and progression of human lung cancers are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that oncogenes such as K-ras, c-myc and c-jun are often activated or overexpressed in human lung cancers (Wodrich and Volm, 1993;Szabo et al, 1996;Osada and Takahashi, 2002). However, the functional consequences of such oncogene activation in the development and progression of human lung cancers are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular biological studies have already shed a great deal of light on the molecular pathogenesis of lung cancers, demonstrating the existence of multiple genetic alterations such as activation of oncogenes and inactivation of tumor-suppressor genes during the processes of carcinogenesis (Osada and Takahashi, 2002). Previous immunohistochemical studies revealed that the c-jun oncoprotein is highly expressed in 31-50% of NSCLC patients (Wodrich and Volm, 1993;Szabo et al, 1996), and may even be upregulated in atypical bronchial epithelium (Szabo et al, 1996), suggesting a role in early events in the pathogenesis of lung cancers although exact functional consequences remain rather elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, molecular biological studies have demonstrated the existence of multiple genetic and epigenetic alterations of oncogenes and tumour suppressor genes in the process of lung carcinogenesis, providing useful information for new therapeutic strategies. Previous immunohistochemical studies revealed that cJun is highly expressed in 31 -50% of non-small cell lung cancer (NSCLC) tissues (Wodrich and Volm, 1993;Szabo et al, 1996), while no immunoreactivity was detected in normal lung counterparts. Taken together with its transforming properties, cJun may have roles in lung carcinogenesis and/or lung cancer growth.…”
mentioning
confidence: 99%
“…Earlier studies (Wodrich and Volm, 1993;Szabo et al, 1996) suggested that c-Jun had a role in early events in the pathogenesis of lung cancers because it was highly expressed in 31 -50% of patients with non-small cell lung cancers (NSCLCs), and it was also upregulated in atypical bronchial epithelium. In a previous study, we showed that TAM67 inhibited lung cancer growth both in vivo and in vitro using NCI-H1299 (H1299) NSCLC cells that expressed TAM67 under the control of an inducible promoter that blocked AP-1 activity (Shimizu et al, 2008).…”
mentioning
confidence: 99%